2013
DOI: 10.1177/0956797612473121
|View full text |Cite
|
Sign up to set email alerts
|

Lay Theories of Obesity Predict Actual Body Mass

Abstract: Obesity is a major public health problem, but despite much research into its causes, scientists have largely neglected to examine laypeople's personal beliefs about it. Such naive beliefs are important because they guide actual goaldirected behaviors. In a series of studies across five countries on three continents, we found that people mainly believed either that obesity is caused by a lack of exercise or that it is caused by a poor diet. Moreover, laypeople who indicted a lack of exercise were more likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 31 publications
0
61
1
1
Order By: Relevance
“…This is an unexpected result because recently some authors have showed in their work that beliefs about the causes of obesity were a good predictor of BMI (McFerran & Mukhopadhyay, 2013). However, we have found that although these beliefs are not related with weight itself, they are linked with body image perception.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This is an unexpected result because recently some authors have showed in their work that beliefs about the causes of obesity were a good predictor of BMI (McFerran & Mukhopadhyay, 2013). However, we have found that although these beliefs are not related with weight itself, they are linked with body image perception.…”
Section: Discussioncontrasting
confidence: 55%
“…The reviewed literature has showed that the beliefs that people have about which are the causes of obesity may be related with their BMI (McFerran & Mukhopadhyay, 2013). According to these authors, whether a person believes obesi-ty is caused by overeating or by a lack of exercise predicts his or her actual BMI.…”
Section: * Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when faced with an opportunity to indulge in less healthy food, people may use justification to allow themselves to eat something without feeling guilty (Prinsen et al, 2016;Taylor et al, 2014). One of the most common justifications is the belief that physical activity can compensate for poor diet quality (Kronick and Knauper, 2010;McFerran and Mukhopadhyay, 2013). This belief stems from a focus on body weight and energy balance, rather than overall diet quality.…”
Section: Food Swampsmentioning
confidence: 99%
“…People hold the ories about seemingly everything, including genetics (Plaks, Malahy, Sedlins, & Shoda, 2012), global warming (Dunlap, 1998), and obesity (McFerran & Mukhopadhyay, 2013). Some of these theories apply to people's own selves, including lay theories about willpower (Job, Walton, Bernecker, & Dweck, 2013;Miller et al, 2012), personality traits (Beer, 2002), and moods (Igou, 2004).…”
Section: Lay Theoriesmentioning
confidence: 99%